Association of Renal Dysfunction With Remote Diffusion-Weighted Imaging Lesions and Total Burden of Cerebral Small Vessel Disease in Patients With Primary Intracerebral Hemorrhage - Xu, Xu-hua; Ye, Xiang-hua; Cai, Jin-song; Gao, Ting; Zhao, Guo-hua; Zhang, Wen-ji; Tong, Lu-sha; Gao, Feng (Frontiers in Aging Neuroscience, 2018)
Objective: Remote diffusion-weighted imaging (DWI) lesions (R-DWIL) found in intracerebral hemorrhage (ICH) patients are considered as an additional marker of cerebral small vessel disease (cSVD). This study aimed to investigate the association of renal dysfunction and R-DWIL, as well as the total burden of cSVD on magnetic resonance imaging among patients with primary ICH. Methods: One hundred and twenty-six consecutive patients were prospectively enrolled. R-DWIL on diffusion-weighted imaging, as well as other imaging markers of cSVD, including lacunes, white matter lesions, cerebral microbleeds, and enlarged perivascular spaces were rated using validated scales. Renal dysfunction was evaluated either by reduced estimated glomerular filtration rate (eGFR) or the presence of proteinuria or increased cystatin C. Results: After adjustments for potential confounders by logistic regression, impaired eGFR (odds ratio [OR] 6.00, 95% confidence interval [CI] 1.73-20.78), proteinuria (OR 3.07, 95% CI 1.25-7.54) and increased cystatin C (OR 2.73, 95% CI 1.11-6.72) were correlated with presence of R-DWIL. A similar association was also found between cystatin C levels (OR 3.16, 95% CI 1.39-7.19), proteinuria (OR 2.79, 95% CI 1.34-5.83) and the comprehensive cSVD burden. Conclusions: Renal dysfunction are associated with the presence of R-DWIL, and total burden of cSVD in patients with primary ICH.